2021
DOI: 10.3390/soc12010005
|View full text |Cite
|
Sign up to set email alerts
|

Involvement and Multi-Sectoral Collaboration: Applying Principles of Health Promotion during the Implementation of Local Policies and Measures—A Case Study

Abstract: Five principles for health promotion (HP) stand out in various forms, providing guidance for HP measures and policy implementation: (1) a broad and positive health concept, (2) participation and involvement of key stakeholders, (3) build action and action competence by involving and empowering target groups, (4) a setting perspective, and (5) equity in health. The purpose of this study is to describe, and critically discuss, how the five HP principles can be applied to structure collaboration processes for imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…[4][5][6] Four articles use the stakeholder dimension [7][8][9][10] Two articles use the collaborative dimension. 11,12 Five articles discuss school health policy, prevention and regulation of internet game disorder, public policy evaluation and literature review of video game addiction policy responses, policymaking interventions and policy strategies for substance abuse in adolescents. [13][14][15][16][17] One article on the analysis of the Juvenile Contraception Law, 18 one article on the literature review on the prevention of mental health disorders.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] Four articles use the stakeholder dimension [7][8][9][10] Two articles use the collaborative dimension. 11,12 Five articles discuss school health policy, prevention and regulation of internet game disorder, public policy evaluation and literature review of video game addiction policy responses, policymaking interventions and policy strategies for substance abuse in adolescents. [13][14][15][16][17] One article on the analysis of the Juvenile Contraception Law, 18 one article on the literature review on the prevention of mental health disorders.…”
Section: Resultsmentioning
confidence: 99%
“…16 Lillefjell and Mass research, 2022 examines multi-sector involvement and collaboration in implementing health promotion principles at the local level. 11 The level of participation and support of Hepatitis C policy-making in Iran was investigated, the conclusion of the study indicated that involvement in Hepatitis C Virus related stakeholder policy-making is generally low and has implications for policymakers and decisions regarding the adoption of more profitable and effective strategies. 8 Literature Review by Kuss, 14 concluded about the importance of relevant government policies for the prevention of IGD (Internet gaming Disorder).…”
Section: Resultsmentioning
confidence: 99%
“…For example, comprehensibility is linked to consistent communication from above in matters that cannot be influenced easily, to enable individuals to "discover structure" and learn the rules of the game [20,23]. On the other hand, possibilities to engage in power-equal inter-group dialogue also adds to comprehensibility by adding individual or group-wise experiences into the common narrative; and by offering opportunities to contextualize experiences with society and societal resources beyond personal experiences [15,23]. This allows for learning more about how they work for "others" and prepares for more flexible use later.…”
Section: Salutogenesis and The Sense Of Coherencementioning
confidence: 99%
“…Challenges in multi-sectoral collaboration are often summarized as matters of "silothinking", characterized by fragmented knowledge, goals, and responsibilities that damage for motivation and poses obstacles for collaboration processes [15]. In a way, a lot of these challenges could be described as "incoherence" (see Figure 2); according to the salutogenic framework.…”
Section: Horizontal Coherence: Multi-sector Collaboration Processesmentioning
confidence: 99%
See 1 more Smart Citation